Made in USA : an americanization in Modern Art, the '50s & '60s - Stich, Sidra; University Art Museum, University of California, Berkeley; The Nelson-Atkins Museum of Art, Kansas City; Virginia Museum of Fine Arts, Richmond (Berkeley : University of California Press, 1987)
Johns, Jasper ; Rivers, Larry ; Leutze, Emanuel ; Wood, Grant ; Lichtenstein, Roy ; Katz, Alex ; Oldenburg, Claes ; Berthot, Jake ; Herms, George ; Wesselmann, Tom ; Matisse, Henri ; D'Arcangelo, Allan ; Kienholz, Edward ; Rauschenberg, Robert ; Rosenquist, James ; Haberle, John ; Warhol, Andy ; Hefferton, Phillip ; Arneson, Robert ; Warhol, Andy ; etc.
Made in USA : an americanization in Modern Art, the '50s & '60s, University Art Museum, University of California, Berkeley, April 4 - June 21, 1987 / The Nelson-Atkins Museum of Art, Kansas City, July 25 - September 6, 1987 / Virginia Museum of Fine Arts, Richmond, October 7 - December 7, 1987
boek